The Effectiveness Analysis of Frontage Road on Jalan Margonda Raya, Depok - Muhammad Fajri Assalam; Andri Irfan Rifai; Mohamad Taufik (Indonesian Journal of Multidisciplinary Science, 2022)
Highways are the central infrastructure that supports land transportation. Therefore, the highway strongly supports various activities and human needs in land mobilization so that it can achieve its goals both in economic and non-economic terms. In particular, on some highways, there is a system that divides the road into two special lanes: the frontage road and the fast lane. This study aimed to assess the effectiveness of the frontage road on Jalan Margonda Raya, Depok. The data retrieval method is to survey directly and retrieve data through CCTV during peak hours on the road. From the results of this study, the average speed of a motorcycle is 26.625 km / h, which is below the standard free current speed based on the 1997 MKJI of 32.64 km / h, while the average speed of light vehicles (angkot) is 9.9375 km / h, which is below the standard free current speed based on MKJI 1997 which is 41.48 km / h and also obtained a saturation degree value of 1.1105 which means that the frontage road on Jalan Margonda Raya has a Level of Service F value. Therefore, it can be concluded that the frontage road on Jalan Margonda Raya has conditions of forced current, low speed, volume above capacity, and long lines (traffic jams).